Triptychon: usability evaluation and implementation of a web-based application for patients’ lab and vital parameters: original research - Kittel, Maximilian; Moorthy, Preetha; Rao, Sonika; Halfmann, Marie; Thiaucourt, Margot; Strauß, Maximilian; Haselmann, Verena; Santhanam, Nandhini; Siegel, Fabian; Neumaier, Michael (Digital health, 2023)
Background - A major challenge in healthcare is the interpretation of the constantly increasing amount of clinical data of interest to inpatients for diagnosis and therapy. It is vital to accurately structure and represent data from different sources to help clinicians make informed decisions. - Objective - We evaluated the usability of our tool ‘Triptychon’ - a three-part visualisation dashboard of essential patients’ medical data provided by a direct overview of their hospitalisation information, laboratory, and vital parameters over time. - Methods - The study followed a cohort of 20 participants using the mixed-methods approach, including interviews and the usability questionnaires, Health Information Technology Usability Evaluation Scale (Health-ITUES), and User Experience Questionnaire (UEQ). The participant's interactions with the dashboard were also observed. A thematic analysis approach was applied to analyse qualitative data and the quantitative data's task completion time and success rates. - Results - The usability evaluation of the visualisation dashboard revealed issues relating to the terminology used in the user interface and colour coding in its left and middle panels. The Health-ITUES score was 3.72 (standard deviation (SD) = 1.0), and the UEQ score was 1.6 (SD = 0.74). The study demonstrated improvements in intuitive dashboard use and overall satisfaction with using the dashboard daily. - Conclusion - The Triptychon dashboard is a promising new tool for medical data presentation. We identified design and layout issues of the dashboard for improving its usability in routine clinical practice. According to users’ feedback, the three panels on the dashboard provided a holistic view of a patient's hospital stay.
Gesehen am 30.01.2024